Sinergitas Pancasila dan Fatwa tentang Etika Dakwah di Era Digital - Islamy, Athoillah (POROS ONIM: Jurnal Sosial Keagamaan, 2023)
The phenomenon of da'wah content on various social media platforms that usher in social conflicts has become a crucial problem in Indonesia. This encourages the government and all elements of society to be able to minimize it. This study intends to identify and explore the dimensions of Pancasila values in the fatwa of the Indonesian Ulema Council of East Java Province Number. 06 of 2022 concerning Da'wah Ethics in the Digital Era. This qualitative study in the form of literature study uses a normative-philosophical approach. The philosophical values contained in Pancasila become a theory of analysis of the subject of study. The data collection of this study uses documentation techniques, and data analysis techniques use the stages of data reduction, presentation, and verification. This study concludes that there is a dimension of Pancasila values in the fatwa of the Indonesian Ulema Council of East Java Province concerning Da'wah Ethics in the Digital Era. First, the value of divinity (religion) and humanity in the prohibition of the delivery of provocative da'wah content. Second, the value of unity in advocating the delivery of pluralist and nationalist da'wah content. Third, the value of democracy and social justice in the recommendation of delivering da'wah content that maintains public conduciveness and stability. The theoretical implications of this study show that the universal values contained in Pancasila can be transformed into Islamic socio-religious fatwas, as well as fatwas related to da'wah ethics in the digital space. The limitations of this study have not identified the effectiveness of the fatwa of the Indonesian Ulema Council of East Java Province on Da'wah Ethics in the Digital Era.